The combination of piper Caninum Blume leaf extract and compost fertilizer for pressing blast disease and improving growth of bali red rice (Oryza Sativa Linn) - Suriani N.L.; Darmadi A.A.K.; Parwanayoni N.M.S.; Hamid M.H.N.A.; Yamin B.M. (Insight Society, 2024)
Indexed by SCOPUS